THE INFLUENCE OF SKILLS, COMMUNICATION, AND SUPPORTING EQUIPMENT OF CONSERVATIVE DENTISTRY SPECIALISTS (DRG. SP.KG) ON WAITING TIME AND ITS IMPLICATIONS FOR PATIENT SATISFACTION (A SURVEY AT KAJEN DISTRICT HOSPITAL, PEKALONGAN) - Jeanny Kathleen Hartini; Kosasih; Etty Sofia; Taufan Nugroho; Vip Paramarta; Farida Yuliaty (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the effects of dentists’ skills, communication, and supporting equipment on waiting time and their implications for patient satisfaction at Kajen Regional General Hospital (RSUD Kajen) in Pekalongan. The research was motivated by long waiting times and limited facilities. A quantitative associative approach was used, with data collected through questionnaires from 286 patients receiving conservative dental care. Data analysis included validity, reliability, multiple regression, and Sobel tests to examine both direct and indirect relationships among variables. The results showed that skills, communication, and supporting equipment significantly influenced waiting time and patient satisfaction, both directly and indirectly. Waiting time was found to mediate these effects. Communication was identified as the most dominant factor affecting patient satisfaction, while supporting equipment played a key role in speeding up treatment and reducing waiting time. Improving dental service efficiency at RSUD Kajen can be achieved by enhancing dentists’ skills and communication, and optimizing modern supporting equipment. These efforts are expected to increase patient satisfaction and support continuous improvement in hospital service quality.